Structural and Chemical Investigation of Water-Soluble Galactomannan Isolated from Seeds of Cassia Sophera: Exploring the Structure and Composition of Water-Soluble Galactomannan from Seeds of Cassia Sophera (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Water-soluble polysaccharides were extracted from seeds of Cassia Sophera. The galactomannan extraction was based on mechanical separation of the endosperm, water dissolution, centrifugation and precipitation with acetone and pet ether. In the current investigation found that a water-soluble galactomannan consisting of D-galactose and D-mannose in the molar ratio 34. Methylation and hydrolysis of the galactomannan produced 2,3-di-0-methyl-D-mannose (2 moles), 2,3,6-tri-0-methyl-D-mannose (3 moles), and 2,3,4,6-tetra-0-methyl-D-galactose (2 mole). Partial acid catalysed hydrolysis of the seed gum gave five oligosaccharides epimelibiose, mannobiose, galactosyl mannobiose, galactobiose and mannotriose. The characterized polysaccrides from the gum has the basic structure of galactomannans with a main chain of (1→4)-linked β-D-mannopyranosyl units to which single α-(1→6)-D-linked galactopyranosyl units.